Rural Modernity in Britain : a Critical Intervention - Bluemel, Kristin (Edinburgh scholarship online., 2018)
Rural Modernity in Britain argues that the rural areas of Britain were impacted by modernisation just as much - if not more - than urban and suburban areas.